2022
DOI: 10.3168/jds.2021-21215
|View full text |Cite
|
Sign up to set email alerts
|

Symposium review: The role of adipose tissue in transition dairy cows: Current knowledge and future opportunities

Abstract: Adipose tissue (AT) is a central reservoir of energy stored in the form of lipids. In addition, AT has been recognized as an immunologically and endocrinologically active tissue of dairy cattle. The recent literature on AT biology of transition dairy cows has often focused on the possible negative effects that originate from excessive body fat. However, the highly efficient energy-storage capability of this tissue is also vital to the adaptability of dairy cattle to the change in nutrient availability, and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 135 publications
(177 reference statements)
0
9
0
Order By: Relevance
“…These health issues are regarded as major management and economic challenges for the dairy industry that can also influence the longterm milk production performance of cows. Excessive lipolysis in transition cows is a multifactorial condition, in which both host metabolism and immune functions are altered [3,4]. However, there is a lack of understanding of associative and causative relationships between host metabolism and immune regulation in transition dairy cows that experience elevated lipolysis.…”
Section: Introductionmentioning
confidence: 99%
“…These health issues are regarded as major management and economic challenges for the dairy industry that can also influence the longterm milk production performance of cows. Excessive lipolysis in transition cows is a multifactorial condition, in which both host metabolism and immune functions are altered [3,4]. However, there is a lack of understanding of associative and causative relationships between host metabolism and immune regulation in transition dairy cows that experience elevated lipolysis.…”
Section: Introductionmentioning
confidence: 99%
“…After calving, the energy intake was not enough to meet the lactating requirement and body fat mobilization was induced by negative energy balance (NEB) [ 54 ]. There was no doubt that the DMI and milk production increased gradually after postpartum (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The net output of NEFA in perinatal adipose tissue depends on the dynamic balance of lipolysis and lipogenesis. Previous studies have shown that perinatal adipose tissue change in dairy cows is a complex process, which includes not only the activation of lipid metabolism pathway in response to nerve and hormone stimulation, but also inflammatory response, immune cell migration, proliferation of some cellular components of stromal blood vessels, and changes of extracellular matrix [ 11 ]. Adipose tissue remodeling will further affect lipid metabolism in adipose tissue by changing the secretion pattern of adipose factors secreted by adipose tissue, and weaken the ability of AT to buffer excessively high concentration of circulating NEFA, thus increasing the risk of metabolic and inflammatory diseases [ 12 ].…”
Section: Introductionmentioning
confidence: 99%